Research on electro-hydraulic composite drive winch and energy recovery system for mobile crane - Xu, Xianggen; Lin, Tianliang; Ren, Haoling; Guo, Tong; Li, Zhongshen; Miao, Cheng (Frontiers in Energy Research, 2023)
Owing to the high power consumption and limited control precision of traditional hydraulic drive winch systems, this study proposes hydraulic and electric-type energy recovery systems. The accumulator used in the hydraulic type has low energy density, which makes it difficult to store a large amount of energy. Meanwhile, the electric motor/generator used in the electric type cannot solve the secondary slip because of oil leakage, which leads to low controllability and high-power consumption under near-zero speed and high torque conditions. Thus, based on electric construction machinery with high-pressure, energy-dense electric energy storage units, this study proposes an electro-hydraulic composite drive winch and energy recovery system and control strategy for mobile cranes. Considering the good control characteristics of the electric motor/generator and the high-power density of the hydraulic accumulator, this hydroelectric composite drive and energy recovery system may solve the secondary sliding challenge and ensure large torque output at near-zero speed. A simulation model of the mobile crane is established to verify the feasibility of the proposed system and control strategy. The research results showed that the system is more efficient at recovering energy when the weight is lowered by a greater distance.